mTORC1 Activation by Loss of Tsc1 in Myelinating Glia Causes Downregulation of Quaking and Neurofascin 155 Leading to Paranodal Domain Disorganization - Shi, Qian; Saifetiarova, Julia; Taylor, Anna Marie; Bhat, Manzoor A. (Frontiers in Cellular Neuroscience, 2018)
Mutations in human Tuberous Sclerosis Complex (TSC) genes TSC1 and TSC2 are the leading causes of developmental brain abnormalities and large tumors in other tissues. Murine Tsc1/2 have been shown to negatively regulate the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway in most tissues, and this pathway has been shown to be essential for proper oligodendrocytes/Schwann cell differentiation and myelination. Here we report that ablation of Tsc1 gene specifically in oligodendrocytes/Schwann cells activates mTORC1 signaling resulting in severe motor disabilities, weight loss, and early postnatal death. The mutant mice of either sex showed reduced myelination, disrupted paranodal domains in myelinated axons, and disorganized unmyelinated Remak bundles. mRNA and protein expression analyses revealed strong reduction in the RNA–binding protein Quaking (Qk) and the 155 kDa glial Neurofascin (NfascNF155). Re-introduction of exogenous Qk gene in Tsc1 mutant oligodendrocytes restored NfascNF155 protein levels indicating that Qk is required for the stabilization of NfascNF155 mRNA. Interestingly, injection of Rapamycin, a pharmacological mTORC1 inhibitor, to pregnant mothers increased the lifespan of the mutant offspring, restored myelination as well as the levels of Qk and NfascNF155, and consequently the organization of the paranodal domains. Together our studies show a critical role of mTORC1 signaling in the differentiation of myelinating glial cells and proper organization of axonal domains and provide insights into TSC-associated myelinated axon abnormalities.